Isolation and identification of Edwardsiellatardafrom the middle intestine of the(Asian catfish)Silurustriostegus(Heckel,1843 - Mansoer, A.J.; Mahdi, S.Sh.; Raesan, Sh.J. (Mesopotamian Journal of Marine Sciences, 2022)
The present study represent a first record of the bacterium Edwardsiellatarda, Enterobacteriaceafrom the middle intestine of the Asian catfish, Silurustriostegus on native studies in Iraq.Twenty five fish were collected during December 2006 from the Garmat Ali River, Basrah City, using seine nets. Sampled fish ranged between 350-750g and250-650 mm. Tenisolates of were bacteriaEdwardsiellatardait is belong to.